Safeguarding India’s Maritime Frontiers : Strategies, Initiatives, and Global Collaborations - Dr. N. Kala; Premanand Narasimhan (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
India’s strategic location in the Indian Ocean region underscores the importance of safeguarding its maritime boundaries and critical sea routes. The Government of India has implemented various initiatives to counter illegal activities such as piracy, smuggling, human trafficking, and terrorism while ensuring the safety of maritime trade and energy supplies. Through advanced surveillance systems like the Integrated Coastal Surveillance System (ICSS), proactive naval operations like Operation Sankalp, and regional collaborations such as the Information Fusion Centre – Indian Ocean Region (IFC-IOR), India has strengthened its maritime security framework. This paper examines these initiatives and presents case studies to highlight their success, focusing on the integration of technology, strategic partnerships, and a robust legal framework.